2021
DOI: 10.1021/acsaelm.0c01103
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive, Flexible H2 Gas Sensors Based on Less Platinum Bimetallic Ni–Pt Nanocatalyst-Functionalized Carbon Nanofibers

Abstract: Flexible electronic gas sensors working at room temperature have acquired enormous attention in recent years due to their suitability to be integrated into various wearable electronic products. In this investigation, we have demonstrated a H 2 gas sensor using less platinum bimetallic nickel−platinum nanocatalyst-functionalized carbon nanofibers (CNFs@Ni−Pt) fabricated on a flexible platform. The flexible CNF@Ni−Pt sensor showed only a negligible decrease in response during mechanical stress under flat (21%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Overlap of the peaks of Ni and Pt further indicates that the nanoparticles are bimetallic in nature. 21,27,28 A close observation of XRD patterns of co-axial bimetallic systems; CFs@AuNPs-PtNPs and CFs@Ni NPs-Pt NPs reveals that the peak corresponding to (111) plane of Pt has shifted to higher Bragg angles. From Figure 2, it can also be confirmed that there is not any peak matching to fcc Ni or NiO for co-axial CFs@Ni NPs-Pt NPs.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Overlap of the peaks of Ni and Pt further indicates that the nanoparticles are bimetallic in nature. 21,27,28 A close observation of XRD patterns of co-axial bimetallic systems; CFs@AuNPs-PtNPs and CFs@Ni NPs-Pt NPs reveals that the peak corresponding to (111) plane of Pt has shifted to higher Bragg angles. From Figure 2, it can also be confirmed that there is not any peak matching to fcc Ni or NiO for co-axial CFs@Ni NPs-Pt NPs.…”
Section: Resultsmentioning
confidence: 95%
“…The lowermost B.E components linked might be ascribed to the zero valent state of metallic platinum NPs. 20,21 The Ni 2p spectrum 40,41 unveiled two weak peaks emerging at 875.2 and 856.41 eV, ascribed to the binding energies of Ni 2p1/2 and Ni 2p3/2 as shown in Figure 6e. Besides, from the XPS spectra it was confirmed that, there were not any further impurity peaks, and the major Pt 4f and Ni 2p peaks confirmed the emergence of Ni NPs-Pt NPs bimetallic NPs on CFs by single-step co-axial electrospinning method.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, low-power, flexible hydrogen sensors were recently developed using graphene [54], carbon nanotubes [55], and organic/inorganic 2D hybrid materials [56,57]. Among these sensors, carbon crystal structures can detect hydrogen quickly based on their high hydrogen sensitivity but readily react with other gases because of their large surface areas [58]. To overcome this limitation, studies have been conducted to evaluate the effects of doping noble metals such as Pd [54,55].…”
Section: Chemiresistive Hydrogen Sensorsmentioning
confidence: 99%